Application of an Integrated Blowout Model System, OILMAP DEEP, to the Deepwater Horizon (DWH) Spill. Issue 1 (15th July 2017) - Spaulding, Malcolm; Li, Zhengkai; Mendelsohn, Daniel; Crowley, Deborah; French-McCay, Deborah; Bird, Andrew
Abstract: OILMAP DEEP, an integrated system of models (pipeline release, blowout plume, dispersant treatment, oil droplet size distribution, and fountain and intrusion), was applied to the Deepwater Horizon (DWH) oil spill to predict the near field transport and fate of the oil and gas released into the northeastern Gulf of Mexico. The model included multiple, time dependent releases from both the kink and riser, with the observed subsurface dispersant treatment, that characterized the DWH spill and response. The blowout model predictions are in good agreement with the available observations for plume trapping height and the major characteristics of the intrusion layer. Predictions of the droplet size distribution are in good agreement with the limited in situ Holocam observations. Model predictions of the percentage of oil retained in the intrusion layer are consistent with independent estimates based on field observations. Highlights: Integrated blowout model including pipeline release, dispersant treatment, oil droplet size, plume, and intrusion components Application of model to Deepwater Horizon spill Extensive validation of model predictions against wide variety of field observations Predictions show impact of dispersant treatment on oil droplet size distribution in the presence of complicated oil release.